Calidad y servicios turísticos en el cantón Penipe, provincia de Chimborazo - Jonathan Rubén, Venegas Núñez (2020)
This research work was carried out in response to the problem called “Poor tourist services of the Penipe canton, province of Chimborazo”, in order to contribute to the tourism development of the canton and its parishes. The independent variable of the investigation is the quality and its dimensions are: The expectations, wishes and perceptions of the tourist. While the dependent variable are tourism services and their dimensions are: Physical facilities, intangible aspects and human talent. The main objective of the research is to evaluate the influence of quality in tourist services of the Penipe canton province of Chimborazo, through three specific objectives: to analyze the influence of expectations, desires and perceptions against the tourist services of the canton. The research is exploratory, descriptive and explanatory, as for the research approach it is mixed (quantitative and qualitative), because it meets the objectives set, the research is non-experimental, correlational and cross-sectional. It is composed of two phases: In the first phase, the sample size is determined, the same one that was randomly selected is 170 national tourists over 18 years of age. In the second phase, the population of 32 collaborators belonging to seven tourist establishments in the canton was taken. To verify the reliability and validity of the instruments, experts were chosen according to their academic background and their knowledge regarding quality and tourist services. When testing the hypothesis, it was demonstrated that the client's expectations influence the tourist services of the Penipe canton, province of Chimborazo.